Ovarian Pregnancy following Intracytoplasmic Sperm Injection and Embryo Transfer: A Case Report. (17th June 2012) - Ramachandran, Amar; Sharma, Swati; Pratap, Kumar; Rajesh, Bhakta; Akhila, Vasudeva; Ramayapally, Akhila; Valiathan, Manna
Abstract : Ovarian pregnancy is a rare form of ectopic pregnancy following ICSI-ET, and the diagnosis depends on the physicians suspicion and experience. Preservation of ovarian tissue during surgery is of utmost importance to preserve fertility. We present a case of ovarian pregnancy who had a successful treatment preserving the ovary.